Sipekernik: Sistem Pemantau Kekeruhan Air dan Pengairan pada Akuaponik Menggunakan Sensor Turbidity, LDR dan Water Level - Nur Aziezah; Walidatush Sholihah; Inna Novianty; Mega Romadhona; Anggi Mardiyono (Sekawan Institut, 2023)
Aquaponics is an alternative to cultivating plants and fish in one place. This technique integrates fish farming with plants. In this case, aquaponic plants utilize nutrients from fish waste. Plants in aquaponics function as a biofilter, which will reduce these toxic substances into substances that are not harmful to fish and supply oxygen to fish-keeping ponds. With this technique, there will be a symbiosis of mutualism or a mutually beneficial cycle. The advantages obtained are the efficiency of water use and the reduction of waste contamination resulting from disposal into public waters. The water recirculation period affects the quality and quantity of fish and plants produced. Turbidity for cultivation should be no more than 25 NTU. Therefore, this tool is designed to detect the turbidity value of fish pond water in order to know the time to drain the pond using a turbidity sensor and regulate water irrigation in aquaponic installations based on light intensity values so that water does not stagnate in the installation pipe. The manufacture of this tool uses several components, such as an Arduino as a microcontroller, LDR (Light Dependent Resistor) sensor functions to turn on and off the pump, turbidity sensor functions to determine the turbidity value of pool water, and water level sensor functions to adjust the water level when draining and filling. pond water. At pump 1, the water will turn on if the intensity value of the LDR sensor is 650. If the turbidity sensor value is 25 NTU, then pump 2 will turn on and dump pool water into the shelter. After the pond water is drained to the specified height level, pump 3 will turn on to fill the fish pond with water. Pump 3 will stop when the water level is > 665.